Pengembangan Kurikulum Operasional Satuan Pendidikan (Kosp) TK Berbasis Kearifan Lokal Kota Tidore Kepulauan - Ida Abdal; Mardia H Rahman; Abdul Rahman Janang (Jurnal Ilmiah Wahana Pendidikan, 2022)
Curriculum development in order to improve the quality of education, among others, by carrying out a curriculum update. The purpose of this study was to determine the operational curriculum of Kindergarten based on local wisdom that was developed suitable for use in the Kemala Bhayangkari PAUD education unit, Tidore Islands City. This research method is a research and development method. Data was collected by means of observation, interviews, field notes, documentation and instrument validation/verification of curriculum documents. The results showed that the development of local wisdom-based curriculum in Kemala Bhayangkari Kindergarten in Kindergarten in Tidore Islands City was reviewed from the cover aspect and the validation sheet obtained an average value of 94.38, the preliminary aspect was 96.25, aspects of the vision, mission and goals. of 91.67 aspects of curriculum organization of 96.50, actualization of school culture of 96.69, planning and learning processes of 95.63 while mentoring, evaluation and professional development amounted to 85.00. From the results of the feasibility analysis obtained, it can be declared valid or very suitable to be used for the Kemala Bhayangkari Kindergarten curriculum in the City of Tidore Islands.